The Effect of Customer Relationship Management and Customer Satisfaction on Customer Loyalty : Customer Relationship Management, Customer Satisfaction, Customer Loyalty - Aprianti, Ine; Nugraha, Taufik; Nurfadilah, Lucy (International Journal of Law Policy and Governance, 2024)
This research is motivated by the phenomenon of a lack of product education, especially updates on the livin by Mandiri application which results in customers being stalled in transactions, not being proactive in exploring the needs of convenience in communication, officers at the branch are considered less communicative, customer service who receive complaints are unable to provide satisfactory answers plus the handling process is so long, it is interesting to know the factors that cause the above problems, This study uses quantitative research methods, the data will be analyzed using Descriptive Analysis, Classical Assumption Test, and Verification Analysis. The sampling method is the Probability Sampling method using the Slovin proportional formula. Based on the analysis that has been done, it is obtained that the average value of 3.57 is included in the good category and the condition of Customer Satisfaction obtained an average value of 3.83 is included in the Good category. The condition of Customer Loyalty obtained an average value of 3.73 is included in the Good category. Partially Customer Relationship Management has a positive and significant effect on Customer Loyalty. partially Customer Satisfaction has a positive and significant effect on the Customer Loyalty variable. simultaneously (F test) Customer Relationship Management and Customer Satisfaction have a positive and significant effect on Customer Loyalty. This is supported This is supported by the results of several tests that have been carried out.